Efektivitas Relaxation Technique dalam Menurunkan Kecemasan pada Pasien Heart Disease - Hapsari, Tutut Riana; Waluyo, Agung; Aryani, Denissa Faradita (Journal of Telenursing (JOTING), 2024)
Introduction: This systematic review aims to determine the effectiveness of relaxation therapy in reducing anxiety in heart disease patients and knowing what relaxation techniques are more effective than other techniques. The method used in this review is a review of various data bases including ProQuest, ScienceDirect and Pubmed published between 2013-2023 with the search keywords Relaxation Technique, Anxiety, Heart Disease. The results showed that there were four articles that showed the effectiveness of relaxation therapy in reducing anxiety in patients with heart disease. Conclusion: Relaxation therapies such as Benson's Relaxation Technique, prayer therapy, TaiChi, Meditation can be used effectively in the management of anxiety in heart disease patients. Keywords: Heart Disease, Anxiety, Relaxation Technique